Socially inclusive and equitable approaches for resilient livestock systems - Bullock, Renee; DuttaGupta, Tanaya; Triana-Angel, Natalia (International Livestock Research Institute, 2024)
Unequal social relations and differentiation can exacerbate livestock farmers’ vulnerabilities to climate change and influence their adaptation capabilities and coping responses to climate change and other shocks. Social dynamics and relations influence and shape how climate impacts are experienced and adaptation opportunities and resilience. Unequal power relations are reproduced and reinforced through adaptation processes. Women, men, youth and marginalized social groups obtain differential access to essential resources that underpin resilience (e.g. services, knowledge and capital). Context-specific factors that significantly influence these processes include geography and rurality, livestock systems, mobility, ethnicity and conflict. Current and relevant context-specific evidence about vulnerabilities and capacities is needed urgently to inform interventions and activities that will support equitable adaptation to enhance resilience.